Transcriptional analysis of defense mechanisms in upland tetraploid switchgrass to greenbugs. Issue 1 (December 2017) - Donze-Reiner, Teresa; Palmer, Nathan; Scully, Erin; Prochaska, Travis; Koch, Kyle; Heng-Moss, Tiffany; Bradshaw, Jeffrey; Twigg, Paul; Amundsen, Keenan; Sattler, Scott; Sarath, Gautam
Abstract Background Aphid infestation of switchgrass (Panicum virgatum ) has the potential to reduce yields and biomass quality. Although switchgrass-greenbug (Schizaphis graminum; GB) interactions have been studied at the whole plant level, little information is available on plant defense responses at the molecular level. Results The global transcriptomic response of switchgrass cv Summer to GB was monitored by RNA-Seq in infested and control (uninfested) plants harvested at 5, 10, and 15 days after infestation (DAI). Differentially expressed genes (DEGs) in infested plants were analyzed relative to control uninfested plants at each time point. DEGs in GB-infested plants induced by 5-DAI included an upregulation of reactive burst oxidases and several cell wall receptors. Expression changes in genes linked to redox metabolism, cell wall structure, and hormone biosynthesis were also observed by 5-DAI. At 10-DAI, network analysis indicated a massive upregulation of defense-associated genes, including NAC, WRKY, and MYB classes of transcription factors and potential ancillary signaling molecules such as leucine aminopeptidases. Molecular evidence for loss of chloroplastic functions was also detected at this time point. Supporting these molecular changes, chlorophyll content was significantly decreased, and ROS levels were elevated in infested plants 10-DAI. Total peroxidase and laccase activities were elevated in infested plants at 10-DAI relative to control uninfested plants. The net result appeared to be a broad scale defensive response that led to an apparent reduction in C and N assimilation and a potential redirection of nutrients away from GB and towards the production of defensive compounds, such as pipecolic acid, chlorogenic acid, and trehalose by 10-DAI. By 15-DAI, evidence of recovery in primary metabolism was noted based on transcript abundances for genes associated with carbon, nitrogen, and nutrient assimilation. Conclusions Extensive remodeling of the plant transcriptome and the production of ROS and several defensive metabolites in an upland switchgrass cultivar were observed in response to GB feeding. The early loss and apparent recovery in primary metabolism by 15-DAI would suggest that these transcriptional changes in later stages of GB infestation could underlie the recovery response categorized for this switchgrass cultivar. These results can be exploited to develop switchgrass lines with more durable resistance to GB and potentially other aphids.